The design of a FPGA-based reconfigurable IP video surveillance and control system. - Ngoc, Nam Pham (Asean Engineering Journal)
This paper presents the HW/SW co-design of a reconfigurable IP video surveillance and control system based on low cost Xilinx Spartan 3E FPGA family. The system allows users to observe video images captured by a camera via any standard browser and control remote devices. Our design focuses on the design of the HW base line JPEG encoder on FPGA and the design of a SW web server running on uCLinux operating system ported on MicroBlaze, a soft-core microprocessor embedded on thje FPGA. With the reconfigurability of FPGA, the system can be upgraded easily to support multiple cameras and more control functionality without incurring high additional design cost.